Navigating digital teaching in Spain during the COVID-19 pandemic: how language teacher educators enhance and integrate digital literacy and resilience - Meltem Eşki; Hugo Santiago Sanchez; Steve Walsh (Cogent Education)
This study explores how three language teacher educators developed digital literacy and resilience during the COVID-19 pandemic. Using qualitative methods, including autobiographical narratives and interviews, the research traces the adaptive strategies these educators employed in online and hybrid teaching. Findings indicate that digital literacy transcends technical proficiency to include critical, pedagogical adaptation, while resilience encompassed emotional regulation and reflective practices. The study shows the critical interplay between these competencies, highlighting the need for professional development that addresses both technical and emotional resilience. These insights offer a valuable framework for supporting educators’ well-being and effectiveness in technology-mediated teaching environments.